Reality of managing occupational safety and health’s human resources in the public sector in the Gaza governorates in Palestine - Al-Ghazali, Samah K. (Journal of Risk and Crisis Management, 2019)
This study aimed to clarify the reality of managing occupational safety and health’s human resources in the public sector in the Gaza governorates in Palestine, and clarify if there is obstacles and challenges that stand against this process, and ways to overcome discovered obstacles and challenges. In order to achieve the objective of the study, researcher had relied on descriptive analytical approach by analyzing the content of job descriptions and the organizational structures of the sample of the study, which included the Ministry of Labor and the General Directorate of Civil Defense. Additionally, researcher had analyzed human resources statistics in the field of occupational safety and health, and human resources management reports in this area such as reports of identifying training needs, performance reports, guides and strategies to develop their skills and competencies. Also, researcher had used personal interview with specialists to strengthen the theoretical framework, analyze results, and develop recommendations The study found that there is a significant deficit in the number of human resources working in the field of occupational safety and health in the sample of the study, with a deficit rate of more than 50%. Also, researcher had concluded that there is there is a weak managerial performance in preparing manuals and guides that concern in building, developing, and organizing the work of occupational safety and health human cadre. Additionally, the current political and economic situation which face Gaza Strip had left its negative effects on the process of managing safety cadre efficiently and effectively. The study had recommended strengthening the current situation of occupational safety and health by rotating current cadre to meet working needs, in addition to the need of allocating sufficient budget for training programs that concerns in building seniors level capabilities in managing safety cadre. In addition to prepare, build, and implement specialized and focused media programs and campaigns that works on improve community awareness of occupational safety and health.